Mechanical behavior and optimization of multidirectional laminate specimens under delamination by bending - Ahmed Benyahia, A.; Laksimi, A.; Ouali, N.; Azari, Z. (Проблемы прочности, 2006)
Delamination in the multidirectional laminates under bending loading is often difficult to characterize because of problems involved by excessive deformations ahead of the crack tip and by non-linearities due to large displacements and transverse microcracking. In fact, these microcracks appear in the most strained plies especially for thin materials. Consequently, the concept of linear elastic fracture mechanic cannot be used in order to characterize delamination. Thus, the objective of this work is to highlight, experimentally and analytically these problems on DCB specimens, then to carry out optimization of thickness which makes it possible to avoid the appearance of transverse cracking before starting of delamination. The material used is E-glass/epoxy multidirectional laminates. The results of optimization obtained are in good agreement with the experimental results. При навантаженні згином багатовимірних ламінатів має місце деламінація. Її опис є досить важким, оскільки у вістрі тріщини присутні великі деформації та відмічаються нелінійні ефекти, що зумовлені значними переміщеннями і утворенням поперечних мікротріщин. Останні з’являються у найбільш навантажених шарах, особливо в тонких ламінатах. Експериментально досліджено вищезгадані особливості на зразках у вигляді консольної балки та виконано оптимізацію товщини багатошарового зразка, за якої деламінація починаєтьсядо утворення поперечних мікротріщин у найбільш навантажених шарах. Об’єктом дослідження служив склоепоксидний зміцнений ламінат. Отримані результати оптимізації товщини зразка добре узгоджуються з експериментальними даними. При изгибном нагружении многомерных ламинатов имеет место деламинация, описание которой весьма затруднительно ввиду наличия больших деформаций у вершины трещины и различных нелинейных эффектов, связанных со значительными перемещениями и образованием поперечных микротрещин. Последние появляются в наиболее нагруженных слоях, особенно в тонких ламинатах. Экспериментально исследованы вышеуказанные особенности на образцах в виде консольной балки и выполнена оптимизация толщины многослойного образца, при которой деламинация начинается до образования поперечных микротрещин в наиболее нагруженных слоях. Объектом исследования служил стеклоэпоксидный упрочненный ламинат. Полученные результаты оптимизации толщины образцов хорошо согласуются с экспериментальными данными.